Pengaruh Voucer Diskon Belanja Pada Live Streaming Aplikasi Tiktok Terhadap Perilaku Implusive Buying Dikalangan Mahasiswa UIN Walisongo Semarang - Vivi Juli Pratiwi; Furqon Efendi; Muchammad Fariz; Khairani Zikrinawati; Zulfa Fahmy (Student Scientific Creativity Journal, 2024)
Technological advances are advancing rapidly, shopping can be done even without leaving the house. Tiktok is one of the online shopping media with the tiktokshop feature. In the tiktokshop application there is a live streaming that is carried out to review the seller's product. In live streaming, it offers discount vouchers that attract the attention of buyers. Teenagers are very easily tempted by voucher offers. This triggers teenagers to do impulsive buying behavior. In this study it was measured using a likert scale. The research subjects were 100 students of Walisongo State Islamic University Semarang. This research uses probability sampling technique. Research using quantitative methods. Based on the research that has been done, the research results show that the significance value is 0.000 (p <0.05) so, there is an effect of shopping discount vouchers on the live streaming application of the tiktok application on impulsive buying in Walisongo State Islamic University Semarang.